Indigenous-led responsible innovation: lessons from co-developed protocols to guide the use of drones to monitor a biocultural landscape in Kakadu National Park, Australia. Issue 2 (4th May 2021) - Macdonald, Jennifer Mairi; Robinson, Cathy J.; Perry, Justin; Lee, Maria; Barrowei, Ryan; Coleman, Bessie; Markham, Joe; Barrowei, Aaron; Markham, Billy; Ford, Henry; Douglas, Jermaine; Hunter, Jatbula; et al.
ABSTRACT: The scholarship and practice of responsibly navigating the disruptive possibilities of new technologies has yet to fully consider Indigenous worldviews. We draw on Indigenous-led research in northern Australia's Kakadu National Park to reflect on research practices for responsibly navigating the introduction of aerial drones as a tool for local Indigenous co-managers to monitor and manage this World Heritage Area. We co-developed protocols to guide Indigenous-led innovation – empowering Indigenous governance, developing ethical and trusted research relationships, and enabling on-going Indigenous-led technological innovation. The protocols were applied to negotiate and navigate the use of drone technology at Jarrangbarnmi, an important biocultural landscape in country owned by Jawoyn people in northern Australia. These protocols provide a way for Indigenous cultural responsibilities for knowledge sharing and stewardship of country to guide and authorise the co-design and application of technological innovations, which are increasingly being used to produce new knowledge to adaptively co-manage Indigenous people's lands and seas.